Caenorhabditis elegans cell biology and physiology - Rothman, Joel H.; Singson, Andrew (Methods in cell biology, 2012)
The second part of an updated edition of the classic Methods in Cell Biology, Volume 48, this book emphasizes diverse methods and technologies needed to investigate C. elegans, both as an integrated organism and as a model system for research inquiries in cell, developmental, and molecular biology, as well as in genetics and pharmacology. By directing its audience to tried-and-true and cutting-edge recipes for research, this comprehensive collection is intended to guide investigators of C. elegans for years to come.--Provided by publisher.